Design of an Information System for Recipients of the Family Hope Program (PKH) at the Office of the Wali Nagari Tebing Tinggi Web-Based: Perancangan Sistem Informasi Penerima Bantuan Program Keluarga Harapan (PKH) Pada Kantor Wali Nagari Tebing Tinggi Berbasis Web - raimon efendi; ides rismanila; yusran yusran (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2022)
The Family Hope Program (PKH) is a program of providing conditional social assistance to very poor families (KSM) designated as beneficiary families of PKH. population welfare. However, to get this PKH assistance, the community must register first by coming directly to the wali nagari office. In this case, it takes a long time for the community to register until the data is received by the village guardian's office. Data collection techniques in this study were carried out by collecting data through observations, interviews and literature studies. The data collected is in the form of PKH participant data and PKH recipient data. Therefore, it is necessary to design a web-based information system for recipients of the Family Hope Program (PKH) for the Tebing Tinggi Wali Nagari Office. With this system, the public can input personal data online, the wali nagari office employees and PKH assistants get data reports online, and the public can view information directly that their names are included in the data of PKH beneficiaries.